The need to reform the law pertaining to rape / Siti Sara Mohd Hussain - Mohd Hussain, Siti Sara (Faculty of Law, 1987)
One of the main tasks of the past decade for women has been to get the world at large, to take times of several violence against women seriously. Violence against women has increased and is advancing. Rape is an act of violence against women. It is a hostile and a sadistic act. It is a violation of a women's autonomy and a negation of her independence. It is not enough to denounce the struggle against the myth of rape as an outcome of passion and overwhelming desire. These myths have to be re-examined This project paper focuses on an offence which has been given a lot of attention by the local mass media and the Joint Women Action Group, that is rape and the need to reform the law pertaining to rape. The calls for official action came from several groups, including the ad-hoc committee of Citizens Against Rape, the Association of Women‘s Lawyers, Gerakan Wanita Movement and the Law Reform Committee of The Malaysian Bar Council.